User Experience-Based Mobile App for Dementia Caregivers: A Case Study in Portoviejo, Ecuador (Innovation & Development in Engineering and Applied Science, 2026)
This work involves the development and implementation of a user-experience-based mobile application designed to support family caregivers of patients with dementia, a disease that affects the cognitive system or mental processes of people, especially those of older age. The participatory action method is used, which involves end users, in this case, caregivers. This method was applied in two phases: initial data collection through interviews and surveys, and subsequently, a prototype of the application was created with iterative feedback sessions from caregivers. In this phase, the Kanban methodology was used, which allowed for changes to be made based on the criteria of 30 people, collected through surveys. This allowed for defining the caregivers' specific needs and building a user-friendly, scalable application with dynamic and easy-to-use interfaces.
Keywords: Mobile app; dementia; Web application; caregivers; prototype